ANALISIS PENDAPATAN USAHATANI BUNGA PEPAYA DI DESA LIKUPANG KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA Farmer Income (Analysis of Papaya Flower in Likupang Village, District of East Likupang North Minahasa Regency) - Pricilia Jenifer Feren Tumigolung; Agnes Estephina Loho; Theodora M. Katiandagho (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to analyze the income and feasibility of papaya flower farming in Likupang Village District of East Likupang North Minahasa Regency. The method that has been used in this study was case study method. The data used in this study was primary and secondary data. Primary data was done by direct interview to farmers by using questionnaire, while for secondary data was done from those who relate, village head office, district office, and also the internet. Data analysis in this study by used farming income and R/C .The result of this research showed that the land area of respondent farmer is 0,8 Ha. The total revenue was Rp8.510.000/month, the total cost was Rp2.253.500/month. The Farmer’s income was Rp6.256.500/month. The of papaya flower farming due to rate of R/C was 3,78.